Peningkatan Pembelajaran Operasi Hitung Nilai Mata Uang Melalui Pendekatan Realistic Mathematics Education (RME) Pada Siswa Disabilitas Intelektual Ringan - Firdika Linda; Arisul Mahdi; Antoni Tsaputra; Syari Yuliana (Jurnal Kajian Ilmu Pendidikan (JKIP), 2026)
This study aimed to enhance students’ currency value calculation skills through the implementation of the Realistic Mathematics Education (RME) approach for learners with mild intellectual disabilities. The research addressed a pedagogical gap related to the limited use of contextual and student-centered mathematics instruction in special education settings, particularly in teaching functional numeracy skills. A Classroom Action Research (CAR) design was employed and conducted in Grade VIII at SLB Workshop Padang, involving two students with mild intellectual disabilities. The intervention was implemented across two cycles, each consisting of planning, action, observation, and reflection stages. Data were collected through performance-based tests and structured observations and analyzed using descriptive quantitative methods. The findings revealed a consistent and meaningful improvement in students’ ability to perform currency value calculations across the two instructional cycles. The results indicate that the RME approach effectively supports conceptual understanding by linking mathematical operations to real-life contexts, thereby enhancing students’ engagement and learning outcomes. This study contributes pedagogically by demonstrating the practical value of RME as a contextual and meaningful instructional approach for teaching functional mathematics in special education classrooms, particularly for students with mild intellectual disabilities.